Sterilized chitosan‐based composite hydrogels: Physicochemical characterization and in vitro cytotoxicity. Issue 1 (3rd October 2019) - Rodríguez‐Rodríguez, Rogelio; Velasquillo‐Martínez, Cristina; Knauth, Peter; López, Zaira; Moreno‐Valtierra, Maira; Bravo‐Madrigal, Jorge; Jiménez‐Palomar, Inés; Luna‐Bárcenas, Gabriel; Espinosa‐Andrews, Hugo; García‐Carvajal, Zaira Y.
Abstract: Gelatin/chitosan/polyvinyl alcohol hydrogels were fabricated at different polymer ratios using the freeze‐drying and sterilized by steam sterilization. The thermal stability, chemical structure, morphology, surface area, mechanical properties, and biocompatibility of hydrogels were evaluated by simultaneous thermal analysis, Fourier transform infrared spectroscopy, X‐ray diffraction, confocal microscopy, adsorption/desorption of nitrogen, rheometry, and 3‐4, [5‐dimethylthiazol‐2‐yl]‐2, 5‐diphenyl tetrazolium bromide cell viability assay (MTT assay), respectively. The samples showed a decomposition onset temperature below 253.3 ± 4.8°C, a semicrystalline nature, and a highly porous structure. Hydrogels reached the maximum water uptake in phosphate‐buffered saline after 80 min, showing values from nine to twelve times their dry mass. Also, hydrogels exhibiting a solid‐like behavior ranging from 2, 567 ± 467 to 48, 705 ± 2, 453 Pa at 0.1 rad/s (low frequency). The sterilized hydrogels showed low cytotoxicity (cell viability > 70%) to the HT29‐MTX‐E12 cell line. Sterilized hydrogels by steam sterilization can be good candidates as scaffolds for tissue engineering applications.